2018
DOI: 10.1093/jas/sky324
|View full text |Cite
|
Sign up to set email alerts
|

Sow stress levels and behavior and piglet performances in farrowing crates and farrowing pens with temporary crating1

Abstract: Farrowing pens with temporary crating have been developed as a compromise between conventional farrowing crates and pens to better accommodate the welfare of both sow and piglets during lactation. However, not much is known about the behavioral and physiological consequences of early removal of confinement on the sow and piglets during lactation. The aim of this study was to assess the effects on sow and piglet performance of temporary crating until 3-d postpartum at 2 times points, immediately after confineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Most earlier studies dealing with stress levels of crated and loose-housed sows in farrowing systems used cortisol measurement in saliva or blood and are, therefore, not directly comparable to this study ( 43 48 ). Lawrence et al ( 43 ) found higher plasma cortisol values around farrowing independent of the housing system.…”
Section: Discussionmentioning
confidence: 78%
“…Most earlier studies dealing with stress levels of crated and loose-housed sows in farrowing systems used cortisol measurement in saliva or blood and are, therefore, not directly comparable to this study ( 43 48 ). Lawrence et al ( 43 ) found higher plasma cortisol values around farrowing independent of the housing system.…”
Section: Discussionmentioning
confidence: 78%
“…King et al [ 33 ] reported mortality to be highest when all crates were opened once the average litter age was 7 days, and suggested opening crates individually, as we did in the current study. Moreover, large litters with small piglets are particularly vulnerable; Goumon et al [ 34 ] found that litter size influenced weight gain in piglets, with larger litters having decreased weight gain. Thus, while opening crates on day 4 for smaller litters with larger, stronger piglets may work, a longer confinement may be beneficial where litters are larger, and piglets within the batch could have a lighter average birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate increased stimulation or stress when the crate is first opened as piglets interact more freely with the sow and the sow becomes more active in the pen. Indeed opening of the crate has been associated with short-time increased restlessness or stress in sows, as well as increased chasing of piglets [ 34 ], which could increase the stress experienced by the piglets. As samples were collected at pen level, this may also be a result of faeces from piglets which could have been mildly injured by the sows increased movement included in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that evaluated the behavior of piglets stress the importance of management effects, considering the type and housing system (Singh et al 2017, Goumon et al 2018, fiber supplementation on pre-weaning diets (Clouard et al 2018), the social environment and interaction of litters (Hong et al 2017), and artificial vocalization (Khonmee et al 2018, Moreira et al 2018. However, the effects of the thermal environment on the suckling behavior of piglets have hardly been explored, although such a characterization of the feeding behavior could serve as the basis for the idealization of strategies (environmental change, sow diet alterations, and animals handling) to ensure an adequate consumption of milk by the piglets, maximizing their survival and performance.…”
Section: Introductionmentioning
confidence: 99%